2014
DOI: 10.1186/1471-230x-14-91
|View full text |Cite
|
Sign up to set email alerts
|

Acid suppressive agents and risk of Mycobacterium Tuberculosis: case–control study

Abstract: BackgroundThe acid-suppressive agents have been linked with an increased risk of infectious disease. The relationship between these drugs and Mycobacterium Tuberculosis (TB) was not been reported.MethodsWe conducted a case–control study using data from National Health Insurance research database of Taiwan. From 1996 till 2008, and 6541 cases were defined as TB infection/activation (ICD-9 coding plus prescription two of four first-line anti-TB regimen for at least one month). Control subjects who were matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
2
22
2
Order By: Relevance
“…Little previous work has been done to investigate the association between PPI use and TB. However, Hsu et al [ 15 ] found an association between acid suppressing medication and an increased risk of TB disease, which on the surface appears at odds with our findings for lansoprazole. However, the association declined to null with increasing duration of therapy with either a PPI or a histamine H2 receptor antagonist.…”
Section: Discussioncontrasting
confidence: 94%
“…Little previous work has been done to investigate the association between PPI use and TB. However, Hsu et al [ 15 ] found an association between acid suppressing medication and an increased risk of TB disease, which on the surface appears at odds with our findings for lansoprazole. However, the association declined to null with increasing duration of therapy with either a PPI or a histamine H2 receptor antagonist.…”
Section: Discussioncontrasting
confidence: 94%
“…The present study indicates that persons with pulmonary tuberculosis were 1.4 times more likely to be exposure to histamine-2 receptor antagonists than those without pulmonary tuberculosis. This finding was compatible with a previous case-control study showing a positive association between tuberculosis and histamine-2 receptor antagonists therapy (OR=1.51; 95% CI 1.50 to 1.52) 5. The case group in our study included subjects with newly diagnosed pulmonary tuberculosis during the period of 2000–2013 (based on International Classification of Diseases 9th Revision-Clinical Modification, ICD-9 codes 010, 011, 012 and 018).…”
supporting
confidence: 91%
“…The proton pump inhibitor omeprazole is effective in several eukaryotic and prokaryotic cells ( da Silva et al, 2011 ) and it also presents antibacterial effects against several bacterial strains including Helicobacter pylori ( Jonkers et al, 1996 ). However, it has been suggested that omeprazole may promote the growth of M. tuberculosis and MAC bacteria due to a high prevalence of infections caused by these bacteria in patients using acid-suppressive agents ( Suzuki et al, 2000 ; Hsu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%